Pengaruh Pengupahan dan Reward Non-Financial Terhadap Kinerja Karyawan Dengan Motivasi Kerja Sebagai Variabel Intervening (Studi Kasus di PT Sembilan Jagad Pandhito (SJP)) - Lianingsih, Laila Nina; Natigor, Dayan Hakim; Rudiyanto, Rudiyanto (Jurnal sosial dan sains, 2025)
This study aims to analyze the effect of remuneration and non-financial rewards on employee performance with work motivation as an intervening variable at PT Sembilan Jagad Pandhito (SJP). The background of this study is the issue of suboptimal employee performance, which is influenced by perceptions of the fairness of the wage system, limitations in the provision of non-financial rewards, and fluctuating levels of work motivation. The research method used is a quantitative approach with data collection through the distribution of questionnaires to 60 PT SJP employees as respondents. Data analysis was performed using Partial Least Square – Structural Equation Modeling (PLS-SEM) with the help of SmartPLS software. The independent variables in this study were remuneration and non-financial rewards, the dependent variable was employee performance, while work motivation acted as an intervening variable. The results showed that remuneration had a positive and significant effect on employee performance. Non-financial rewards were also found to have a positive effect on performance, both directly and through work motivation. In addition, work motivation mediates the relationship between remuneration and non-financial rewards with employee performance. These findings confirm that PT SJP needs to design a fair, timely, and standard-compliant remuneration system and strengthen consistent non-financial reward policies in order to increase work motivation and produce optimal performance.